Analisis Kelengkapan Formulir Ringkasan Masuk dan Keluar Pada Rekam Medis Pasien Rawat Inap: (Studi Kasus Di RSKIA Ummi Khasanah Bantul Daerah Istimewa Yogyakarta) - Intan Sukmawati; Yudi Siyamto; Khoiri Najib (Nur Science Institute, 2023)
This study aims to describe the completeness of the admission and discharge summary forms in terms of patient identification, important reporting, authentication, and documentation in the medical records of inpatients. The research method used is descriptive method using quantitative analysis methods. The Simple Random Sampling technique was used in this study with a sample of 163 incoming and outgoing summary forms out of a total population of 274 incoming and outgoing summary forms. The results of this study showed that based on patient identification completeness was 78% and incompleteness reached 22%, important reporting with a completeness rate of 67% and 33% incompleteness, authentication with a completeness rate of 99% and 1% incompleteness, as well as correct documentation with a completeness level 94% and 6% incomplete. So that the results of the study show that the percentage of completeness of filling in the summary forms of admission and discharge in the medical records of inpatients at RSKIA Ummi Khasanah Bantul Daerah Istimewa Yogyakarta is still not 100% with a percentage of completeness of 84% and incompleteness of 16%.